Educating SMAN 97 Jakarta Teachers About the Consumption of Herbs and Vitamin C During the COVID-19 Pandemic - Febrial Hikmah; Nur Hasanah; Agung Dewantoro; Anggraini Karditiawati; Dony Mahendra; Novita Rahmadhani; Melda Yunisa (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Self-medication, with both herbs and vitamin C, is the community’s choice in dealing with the COVID-19 pandemic. Herbs are believed to have many properties that have been tested historically and empirically. Meanwhile, vitamin C has been shown to be clearly able to boost the body’s immune system. Teachers, as the vanguard in educating the education of the nation’s successors, have a very large role in the progress of the Indonesian nation. Teacher health is essential in shaping a dynamic learning process, especially during the COVID-19 pandemic. The purpose of this Community Service activity is to provide education related to knowledge and understanding of the consumption of herbs and vitamin C to prevent the occurrence of adverse drug reactions, especially in teachers of SMAN 97 Jakarta who self-study herbal herbs and vitamin C during the COVID-19 pandemic. This method of Community Service activities is carried out through interactive webinars online. A pretest and posttest will measure the participant’s knowledge before and after counselling. The results obtained in the implementation of community service activities, namely the knowledge and understanding of SMAN 97 Jakarta teachers on the consumption of herbs and vitamin C during the COVID-19 pandemic, increased by an average of 25 points after exposure to the material.